Credit where credit is due - Bruce, Ashley ([S.l.] : TVE, 2004)
This video viewed the effects of'micro credit' in the lives of village women such as Jahanara, Bilkis, Nargis, Minara, Mageda and Shonda. Term'micro credit' means prociding loans to poor people whom the banks won't lend. All of them stayed at one of the district in Bangladesh.
Executive producer, Jenny Richards, Editor, Sofira Kyriacou